Psychosocial Working Condition of Construction Labor Working in Subdivision Housing Project - Suriyanon, Natee (Srinakharinwirot University Engineering Journal, 2020)
This research examined the perceptions of the construction labors working in subdivision housing project on three psychosocial factors, classified labors according to their psychosocial working condition statuses, and tested the relationship between samples’ personal characteristics and their psychosocial working conditions statuses. The samples of this research were 438 workers working in eight housing estate projects in Bangkok, which had selling price between 2.50 million baht and 5.00 million baht. Data was collected in October 2018. Samples perception scores of the psychological demand, the control latitude and the social support analyzed from the survey data had the mean values of 2.96, 2.96 and 3.04, respectively. Proportion of the samples in the psychosocial working condition statuses that causes high strain isolated, high strain collective, active behavior, low stain, and passive behavior were 16.21 %, 21.24 %, 21.46 %, 21.23 %, and 19.86 %, respectively. Results from Chi-Square test indicated that gender, age, education level, nationality, work experience, type of employment, position, and average monthly income are labor’s personal characteristics that were significantly related with psychosocial working conditions status of the labor.